INTEGRITAS PERANGKAT DESA DALAM PENGELOLAAN DANA DESA (STUDI KASUS : KANTOR DESA MINTA KASIH KECAMATAN SALAPIAN KABUPATEN LANGKAT) - Putri, Riska Aulia (JUBISMA, 2023)
This study uses a descriptive qualitative approach, with observational and interview data collection methods, Data analysis in this journal article research applies techniques from miles and huberman by examining using 3 steps, namely: data reduction, data presentation and conclusions, From the results and discussions stated above, it can be seen that: The integrity value of the village office apparatus asking for love still cannot be accounted for Answer The village development program for Minta Kasih is the construction of hamlet borewells, the inclusion of small alley roads and Rehan hamlet village hall. Lack of principles of openness, good accountability and lack of understanding of accounting science The quality standards of the roads used are not in accordance with the expectations of the people of Minta Kasih village With the budget obtained, the village apparatus should be able to try to buy even better quality materials